Evaluation of valvular calcifications in ambulatory dialysis patients - Mircea Călin Țandrău; Cristina Vîrjan; Oana Știrbu; Daniela-Adriana Oatiș (Romanian Medical Journal, 2020)
Valve calcifications are frequently associated with chronic terminal kidney disease (CTKD).There is a direct relationship between valvular calcifications and increased risk for cardiovascular events, respectively increased mortality in patients with CTKD. The aim of the study was to evaluate by Doppler echocardiography (ECoD) the prevalence of cardiac and valvular calcifications in patients with CTKD treated by hemodialysis (HD), and to correlate the data obtained with conventional and specific risk factors and the impact that valvular calcifications have on cardiovascular dysfunction with implications for morbidity and mortality. The study included 203 patients on dialysis with CTKD, aged between 20 and 84 years, who were monitored for a period of 48.5 ± 19.0 months in Arad County. On the studied group, the main etiologies for CTKD were chronic glomerulonephritis in 32% of patients, and diabetes in 22% of cases. A total of 322 calcifications were documented, of which valvular calcifications were estimated to have an incidence between 28% and 55% for the aortic valve and 56% for the mitral valve. Valvular calcification is associated with extensive atherosclerosis of the coronary arteries and aorta. Additional atherogenetic factors such as hypercholesterolemia, diabetes, hypertension and smoking were common. Some probable mechanisms such as increased mechanical stress due to hypertension, chronic volume overload, chronic inflammation, sympathetic hyperreactivity, lipid oxidation contribute to the appearance of vascular calcifications. Also, the number of cardiac calcifications correlates with the duration of the history of hypertension, regardless of whether or not the patient was still hypertensive at the time of the examination. Highlighting the valvular calcifications and intuiting the pathophysiological mechanisms that contribute to their appearance may be factors influencing the therapeutic behavior applied to dialysis patients. Given the large number of patients in whom calcifications were highlighted by echocardiography, it can be concluded that this method is particularly useful in detecting valvular calcifications in ambulatory dialysis patients.